Understanding optimal cadence dynamics: a systematic analysis of the power-velocity relationship in track cyclists with increasing exercise intensity - Dunst, Anna Katharina; Hesse, Clemens; Ueberschär, Olaf (Frontiers in Physiology, 2024)
Background: This study aimed to investigate the change in force-velocity (F/v) and power-velocity (P/v) relationship with increasing work rate up to maximal oxygen uptake and to assess the consequent alterations in optimal cadence, particularly at characteristic metabolic states.Methods: Fourteen professional track cyclists performed submaximal incremental tests, high-intensity cycling trials, and maximal sprints at varied cadences (60, 90, 120 rpm) on an SRM bicycle ergometer. Linear and non-linear regression analyses were used to assess the relationship between heart rate (HR), oxygen uptake (V ̇O2), blood lactate concentration (BLC), and power output at each pedaling rate. Work rates linked to various cardiopulmonary and metabolic states, including lactate threshold (LT1), maximal fat combustion (FATmax), maximal lactate steady-state (MLSS) and maximal oxygen uptake (V ̇O2max), were determined using cadence-specific inverse functions. These data were used to calculate state-specific force-velocity (F/v) and power-velocity (P/v) profiles, from which state-specific optimal cadences were derived. Additionally, fatigue-free profiles were generated from sprint data to illustrate the entire F/v and P/v continuum.Results: HR, V ̇O2 demonstrated linear relationships, while BLC exhibited an exponential relationship with work rate, influenced by cadence (p<0.05, η 2 ≥0.655). Optimal cadence increased sigmoidally across all parameters, ranging from 65.80±3.53 rpm at LT1, 76.06±3.18 rpm at FATmax, 82.45±3.10 rpm at MLSS, culminating at 84.35±2.78 rpm at V ̇O2max (p<0.01, η 2 =0.910). A fatigue-free optimal cadence of 135±11 rpm was identified. Sprinters and endurance athletes showed no differences in optimal cadences, except for the fatigue-free optimum (p<0.001, d=2.215).Optimal cadence increases sigmoidally with exercise intensity up to maximal aerobic power, irrespective of the athlete's physical condition or discipline. Threshold-specific changes in optimal cadence suggest a shift in muscle fiber type recruitment toward faster types beyond these thresholds. Moreover, the results indicate the need to integrate movement velocity into Henneman's hierarchical size principle and the critical power curve. Consequently, intensity zones should be presented as a function of movement velocity rather than in absolute terms.